KUALITAS HIDUP PEREMPUAN MENOPAUSE - Anggia Kargenti Evanurul Marettih (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2012)
Menopausal problems related to physical and psychological aspects. Physical aspects, declining estrogen production leading to many reproductive disorders such as irregular menstruation (3-4 years before menopause), blooding to vasomotor disturbances that can affect the activities of women experiencing menopause. Psychological, menopausal women will experience emotional instability, along with concerns that might occur in the body with the end of her menstrual period. Emotional stability will be gained back once they get good information about the menopause. Positive self-concept as well as the support given by family and friends will be able to improve the quality of life for postmenopausal women. Consistency of self-concept will increase harmonization within the individual, which in turn will increase the happiness of individuals. Individual's quality of life will improve when there is an integration between self-esteem, self-concept, self-acceptance as well as the individuals of understanding and addressing the problems of life.